Sources of national identity of Kurds = Źródła tożsamości narodowej Kurdów - Pochyły, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Kurds as a nation has always Bern self-reliance. Nomadic style of life and ability to survive hostile attacks made them very valuable a mercenaries in many wars conducted by their neighbours. Kurdistan was also some kind of a buffer where many contradicted interests and politics has been set against each other. Kurds profess islam, they speak in a few dialects of kurdish lanuguage and live today in 4 countries in the Middle East (Iraq, Iran, Turkey, Syria). Kurds in Iraq have Autonomy with president, government, parliament, police and army. They are dreaming about future and independent Kurdystan.
Keywords: Kurds; Kurdystan; identity; origin; language; Kurdowie; tożsamość; pochodzenie; język